2022
DOI: 10.1002/fsn3.3180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistance and determination of stability of different sugar beet (Beta vulgaris L.) genotypes in rhizomania‐infected conditions

Abstract: Plant diseases are considered one of the main factors reducing yield and quality of crops, which are constantly developing and creating more virulent races and cause the resistance of more genes to break. Identifying resistance sources and including them in breeding programs will improve resistant genotypes. Rhizomania is the most common, widespread, and devastating disease of sugar beet in Iran and worldwide.Breeding genotypes with disease resistance genes is one of the most important ways to deal with this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In another study using AMMI model, the first IPC was significant and explained about 63% of GEI variation 34 . Rajabi, et al 40 also reported the significant effect of first six IPCs explaining 98.80% of the total GEI variations. The biplot of mean performance versus WAAS which is called the WAAS biplot (Figure 2), unlike AMMI model which considers only the first IPC, shows stability based on all scores of the IPCs.…”
Section: 1| Additive Main Effects and Multiplicative Interaction (Ammi)mentioning
confidence: 89%
See 1 more Smart Citation
“…In another study using AMMI model, the first IPC was significant and explained about 63% of GEI variation 34 . Rajabi, et al 40 also reported the significant effect of first six IPCs explaining 98.80% of the total GEI variations. The biplot of mean performance versus WAAS which is called the WAAS biplot (Figure 2), unlike AMMI model which considers only the first IPC, shows stability based on all scores of the IPCs.…”
Section: 1| Additive Main Effects and Multiplicative Interaction (Ammi)mentioning
confidence: 89%
“…Sharifi, et al50 used the MTSI in the evaluation of yield and other agricultural traits in a set of rice genotypes and showed that this index is able to identify superior genotypes in terms of yield stability and other agricultural traits. Based on the MTSI results, Rajabi, et al40 introduced five sugar beet genotypes as stable genotypes under field condition infected with rhizomania disease. These results were consistent with the findings obtained from this study regarding the efficiency of MTSI in identifying superior genotypes.…”
mentioning
confidence: 99%
“…In a study conducted using the AMMI, the IPC1 was significant and explained about 63% of the data variation (16). In Rajabi, Ahmadi (18) study, the first six IPCs had a significant effect and explained 98.80% of the total variations in GEI.…”
Section: Additive Main Effects and Multiplicative Interaction (Ammi)mentioning
confidence: 90%
“…Methods for the analysis of phenotypic stability are constantly evolving to provide more precision in the assessment of genotypes and the study of environmental interaction components. In phenotypic stability analysis, a combination of several stability analysis methods is often used instead of relying on a single analysis (16)(17)(18)(19).…”
Section: | Backgroundmentioning
confidence: 99%
“…Therefore, identifying and managing these effects is essential for breeding programs (El-Soda et al 2021). Previous studies mentioned the interaction between genotype and environment as significant in evaluating sugar beet genotypes (Ebmeyer et al 2021;Taleghan et al 2023;Rajabi et al 2022) The analysis revealed that the significant main components for the examined traits ranged from 4 to 5. The first four components were significant (p≤ 0.01), explaining 88% of RY's GEI variation.…”
Section: Additive Main Effects and Multiplicative Interaction (Ammi)mentioning
confidence: 99%